A case study of two teachers' understanding of and attitudes towards bilingualism and multiculturalism in a South African primary school - Sutton, Candace (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2006)
At present, there is an emphasis in South African education on promoting multicultural classrooms in schools. This thesis examines the classroom culture of a South African English-medium school, where the majority of the learners are Second Language English learners. It first describes, in the form of a case-study, how two teachers have constructed the culture of their foundation phase classrooms. It then considers why the two teachers have constructed their classrooms in such ways by exploring their knowledge and understanding of, and attitudes towards, multiculturalism, second language acquisition and multilingualism. The study also briefly considers whether teacher training has sufficiently prepared these teachers for the challenges of a multicultural classroom. The data is discussed in terms of education and second language acquisition theory and South African education and language policies. The results of this study indicate that for the most part the classroom culture is distinctly Western and that the teachers have two fundamental assumptions that underpin their action and classroom construction. The first is that a lack of exposure to English is the primary cause of language problems for L2 learners and the second is that the L1 does not need to be maintained or promoted in the school environment because learners are sufficiently exposed to their L1 in the home. The thesis concludes that shortcomings in training and information encourages these two assumptions to take root and that more in-service training that focuses specifically on the nature of second language acquisition and multiculturalism is necessary.
Keywords: Bilingualism in children; English language -- Study and teaching (Elementary) -- Foreign speakers; English language -- Study and teaching (Elementary) -- South Africa; Education, Bilingual -- South Africa; Language and languages -- Study and teaching; Language policy -- South Africa; Multicultural education -- South Africa; Language and education -- South Africa; Multiculturalism